INFLUENCE OF BOARD OF MANAGEMENT’S MOTIVATIONAL STRATEGIES ON KCPE PERFORMANCE IN PUBLIC PRIMARY SCHOOLS OF MIGORI SUB COUNTY IN MIGORI COUNTY, KENYA - Opande, Maurice Ojanga; Kathuri, Prof. Nephat J.; Bahati, Sabina Mureithi (IJRDO - Journal of Applied Management Science, 2017)
Management is the process of acquiring and utilizing resources in order to achieve organizationalgoals. It is a process that can be taken by an individual or individuals to coordinate the activitiesof others in order to achieve set organizational goals. This study was aimed at investigating theinfluence of Board of Management’s motivational strategies on KCPE performance in publicprimary schools of Migori Sub County, Migori Count. Results showed that the level ofsupervision, recognition, working environment and rewarding teachers/learners determinedlearners’ performance in KCPE.